2017
DOI: 10.1080/02713683.2016.1264607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravitreal Bevacizumab, Intravitreal Ranibizumab and Laser Photocoagulation for Treatment of Type 1 Retinopathy of Prematurity in Turkish Preterm Children

Abstract: IVB, IVR and LP are options that can successfully treat ROP. Myopia was observed to be the main refractive error in all treatment groups. Vascularization of the retina was completed later in the IVB group than in the IVR group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
2
23
0
2
Order By: Relevance
“…An analysis of the two groups showed that the gestational age and birth weight were significantly lower in the anti-VEGF treatment group than that in the laser treatment group. This result is similar to other reports [ 8 , 44 , 53 57 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An analysis of the two groups showed that the gestational age and birth weight were significantly lower in the anti-VEGF treatment group than that in the laser treatment group. This result is similar to other reports [ 8 , 44 , 53 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…Retinal laser photocoagulation is a standard treatment for ROP. However, it can result in many problems, such as a wide range of retinal damage and the loss of vision in the photocoagulation area, and is not suitable for some patients, such as those with ROP in zone 1 or AP-ROP [ 44 46 ]. Anti-VEGF drugs may reduce complications when treating ROP.…”
Section: Discussionmentioning
confidence: 99%
“…They could not find a difference between the two groups. Kabataş et al [27] investigated the effects of bevacizumab, ranibizumab, and laser photocoagulation for the treatment of ROP. They found that treated eyes had a more myopic refraction than spontaneously regressed eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal injection of anti-vascular endothelial growth factor (VEGF) antibodies is an alternative to laser treatment in severe cases of ROP, such as aggressive posterior ROP (APROP), and ROP in zone 1 or posterior zone 2 [6]. Different from laser treatment, anti-VEGF antibody injection may allow maturation of the peripheral retina and anterior segment, and reports indicate better structural and visual outcomes (median VA of 0.3 log-MAR at around 2 years after treatment for type 1 ROP [7]) and a reduced incidence of myopia compared with laser [6,[8][9][10][11][12][13][14][15][16], though not all studies support these findings [17,18]. Anti-VEGF antibody therapy may require more than one treatment application, with reported retreatment rates ranging from 4 to 14% [6,9,11,12], though higher rates of 27% have also been reported [7].…”
Section: Introductionmentioning
confidence: 99%